PENGARUH IKLIM ORGANISASI DAN KEPEMIMPINAN YAYASAN TERHADAP KEPUASAN KERJA DAN DAMPAKNYA PADA KOMITMEN ORGANISASI (Studi Kasus Pada Guru Yayasan Pendidikan Pasiad di Jakarta) - Gurgen, Ismail (EKOBISMAN : JURNAL EKONOMI BISNIS MANAJEMEN, 2016)
This report aims to understand effects of climate organization and foundation satisfaction leadership to work impact on the organization commitment on PASIAD foundation .This research is explanative quantitative .The population research is employees foundation PASIAD totaling 125 the and those used about 125 respondents , using sampling census .The methodology this used is path analysis. The result showed that the results of research using analysis the show that the climate the organization have an influence upon satisfaction PASIAD foundation in JAKARTA .Leadership foundation have had a positive impact on work satisfaction .This really shows you thing with a culture of the organization that have been carried out by the company to give satisfaction teacher at PASIAD foundation .Testing on variable influence climate organization against the commitment of the results that the climate organization had an influence on the commitment of the organization .The results of the study show that the foundation PASIAD leadership have had a positive impact on the commitment of the organization .With leadership applied by the foundation, it would impact on improving the commitment an organization of employees. Keywords: organization climate, leadership , job satisfaction , organization commitment